Numerical simulation of deflagration-to-detonation transition in large confined volumes. (July 2015) - Hasslberger, Josef; Boeck, Lorenz R.; Sattelmayer, Thomas
Abstract: A methodology for the computationally efficient CFD simulation of hydrogen-air explosions (including transition to detonation) in large volumes is presented. The model is validated by means of the largest ever conducted indoor DDT experiments in the RUT facility. A combination of models is proposed with a particular focus on the influence of flame-instabilities, especially of thermal-diffusive nature, which are crucial for very lean mixtures. Excellent agreement is achieved in terms of flame acceleration. The quality of DDT predictions itself depends on the underlying mechanism. Whereas DDT by shock-focusing is successfully simulated on under-resolved meshes, DDT by local explosions in the vicinity of the turbulent flame brush remains a challenge. Adaptive mesh refinement therefore emerges as a key technique to resolve more of the essential phenomena at reasonable computational costs affordable by industry. Finally, a generic case demonstrates the influence of mixture inhomogeneity, which can promote flame acceleration and ultimately DDT. Highlights: CFD simulations of hydrogen-air explosions in large confined volumes are presented. Adaptive mesh refinement is a key technique to minimize computational costs. The model is successfully validated by large-scale experiments in the RUT facility. Safety-relevant lean mixtures close to the lower detonation limit are considered. The influence of mixture inhomogeneity on flame acceleration and DDT is discussed.